2019
DOI: 10.1097/njh.0000000000000555
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Nursing Students’ Attitudes Toward End-of-Life Care

Abstract: End-of-life care is an important nursing competency and must be incorporated into the baccalaureate nursing curriculum. The purpose of this research was to examine the outcomes of an actual hospice compared with a simulated hospice clinical experience. This pretest and posttest nonequivalent 2-group design consisted of a sample of 65 undergraduate nursing students enrolled in a community health course. All students enrolled in the community health course have 1 day for hospice experience and a 2-hour orientati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
0
11
0
7
Order By: Relevance
“…Without acquiescence that life comes to an end, it is enormously, perhaps impossibly, difficult to provide good end-of-life care. One study concluded that nursing students do not have a negative attitude toward caring for dying patients [ 6 ]. Some studies demonstrates that the didactic and clinical experiences of end-of-life care in nursing programs were inadequate due to the denial of death [ 49 , 50 ] However, previous study showed that death education can change both students’ and patients’ attitudes toward death [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Without acquiescence that life comes to an end, it is enormously, perhaps impossibly, difficult to provide good end-of-life care. One study concluded that nursing students do not have a negative attitude toward caring for dying patients [ 6 ]. Some studies demonstrates that the didactic and clinical experiences of end-of-life care in nursing programs were inadequate due to the denial of death [ 49 , 50 ] However, previous study showed that death education can change both students’ and patients’ attitudes toward death [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confidentiality and anonymity were ensured, and a semi-structured interview guide was used to elicit information about participants’ experiences of end-of-life care education [ 7 ]. An interview guide was developed based on the literature [ 6 , 27 ] and the clinical expertise of the authors. To eliminate disruptions, the interviews were conducted in the setting preferred by each participant and were arranged at a date and time convenient for the participant.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Los estudios se desarrollaron con estudiantes de pregrado de enfermería y medicina. Las simulaciones en algunos de los estudios impartieron conocimientos en CP (22)(23), conceptos básicos para enfermería y medicina en CP (24), evaluación y manejo de síntomas (23,25), comunicación terapéutica (22)(23)(25)(26), cuidado interdisciplinar para el paciente y la familia (23)(24)(25)27), opciones en la atención al nal de la vida CP (22,24), espiritualidad (22,24,27,28), aspectos culturales (28) y cómo abordar las discusiones acerca de la muerte con el paciente y la familia (22). Tres estudios fundamentaron su contenido en tres marcos teóricos para el desarrollo de competencias en enfermería, una de ellas llamada Chaarm, que recomienda que el personal de enfermería debe ser compasivo, holístico, atento, adaptable, realista / resuelto y moral (23).…”
Section: Estrategias De Simulación En Cpunclassified
“…Palliative care teams have affinity through a shared vision of compassion, and a commitment to the relief of suffering and to overall improvement in healthcare delivery (Dahlin et al, 2019). Nurses have always played a central role in the care of dying patients (Mahan et al, 2019), and they have a unique key role attending to the nature of care they provide. Nurses are the healthcare professionals who are most willing to be present and best able to articulate what dying patients most need.…”
Section: End-of-life Time and Nursing Carementioning
confidence: 99%